2002
DOI: 10.1002/jnr.10242
|View full text |Cite
|
Sign up to set email alerts
|

Δ9‐tetrahydrocannabinol increases endogenous extracellular glutamate levels in primary cultures of rat cerebral cortex neurons: Involvement of CB1 receptors

Abstract: The effects of the principal psychoactive component of marijuana, Delta(9)-tetrahydrocannabinol (Delta(9)-THC), on endogenous extracellular glutamate levels in primary cultures of rat cerebral cortex neurons were investigated. Locally applied Delta(9)-THC (0.03, 3, 300, and 1,000 nM) concentration-dependently increased basal extracellular glutamate levels (+18% +/- 11%, +54% +/- 10%, +90% +/- 14%, +149% +/- 33% vs. basal). The facilitatory effects of Delta(9)-THC (3 and 300 nM) on cortical glutamate were fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
9
0
3
Order By: Relevance
“…This view is strengthened by the abundant perisomatic expression of CB 1 Rs in neocortical and PFC interneurons (Tsou et al, 1998;Marsicano and Lutz, 1999). Also, cannabinoids have been shown to increase cortical excitatory transmission and net spiking probability of pyramidal neurons in vivo (Pistis et al, 2001;Fortin et al, 2004), consistent with a concurrent increment of basal glutamate levels and decrement of basal GABA levels in prefrontocortical microdialysis experiments observed in anesthetized (Pistis et al, 2002) and awake (Ferraro et al, 2001) rats, as well as in prefrontocortical in vitro culture (Ferraro et al, 2001;Tomasini et al, 2002).…”
Section: Discussionmentioning
confidence: 66%
“…This view is strengthened by the abundant perisomatic expression of CB 1 Rs in neocortical and PFC interneurons (Tsou et al, 1998;Marsicano and Lutz, 1999). Also, cannabinoids have been shown to increase cortical excitatory transmission and net spiking probability of pyramidal neurons in vivo (Pistis et al, 2001;Fortin et al, 2004), consistent with a concurrent increment of basal glutamate levels and decrement of basal GABA levels in prefrontocortical microdialysis experiments observed in anesthetized (Pistis et al, 2002) and awake (Ferraro et al, 2001) rats, as well as in prefrontocortical in vitro culture (Ferraro et al, 2001;Tomasini et al, 2002).…”
Section: Discussionmentioning
confidence: 66%
“…Rimonabant blocks the effects of THC in vitro (Rao et al 2004;Tomasini et al 2002), in animals (Compton et al 1996;Tseng and Craft 2004), and in humans . Furthermore, rimonabant has been shown in animals to modulate cannabinoid signaling in the reward circuitry in the brain (Le Foll and Goldberg 2005), thereby reducing opioid self-administration ), relapse to methamphetamine seeking (Anggadiredja et al 2004) or cocaine seeking (De Vries et al 2001), and alcohol self-administration (Arnone et al 1997;de Fonseca et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as both cannabinoids (Shen and Thayer 1999;Pistis et al 2002;Tomasini et al 2002) and HIV (Ferrarese et al 2001;Chang et al 2002) have been shown to affect the glutamatergic system, we also expected to observe interactive effects between HIV and chronic marijuana use on brain glutamate concentrations.…”
Section: Introductionmentioning
confidence: 99%